2019
DOI: 10.1177/000313481908501027
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Prescribed Opioids after General Surgery Procedures at a Public Hospital

Abstract: Overdose of opioids is the number one cause of accidental death in the United States, and surgeons are overprescribing these medications. The aim of this study was to assess the feasibility of implementing postoperative opioid prescribing guidelines for general surgery procedures at a public hospital, where patients have lower socioeconomic status, public insurance, and limited access to care. We implemented a quality improvement project, which included in-service training for surgical staff and distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“… 15 Recent opioid prescribing recommendations for patients undergoing a laparoscopic cholecystectomy range from 0 to 15 oxycodone or equivalent pills. 16 17 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Recent opioid prescribing recommendations for patients undergoing a laparoscopic cholecystectomy range from 0 to 15 oxycodone or equivalent pills. 16 17 …”
Section: Methodsmentioning
confidence: 99%
“…Among a recent cohort of patients undergoing both laparoscopic cholecystectomies and appendectomies, the average number of opioid pills taken postdischarge was 1.8 oxycodone pills 15. Recent opioid prescribing recommendations for patients undergoing a laparoscopic cholecystectomy range from 0 to 15 oxycodone or equivalent pills 16 17…”
Section: Methodsmentioning
confidence: 99%
“…16 – 18 Infographics and visuals about pain management with easy to understand language can also be useful in the preoperative setting. A recent single-institution study by Angelo et al 19 showed that a patient-friendly infographic in the preoperative area listing the common “do’s and don’ts” of pain medications was a useful adjunct to help decrease opioid consumption postoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…Easy to follow instructions and patient infographics for pain after surgery can be used to reinforce the importance of these topics. 19 Equally important, the older adult should be counseled on mobility exercises (eg, daily walking program) to perform after discharge to prevent functional decline and must be informed that these may also be associated with some pain and discomfort. 84 At the same time, it is important that the older adult treats his or her pain adequately so as to not impair function.…”
Section: Methodsmentioning
confidence: 99%
“…There is reliable evidence the introduction of opioid guidelines for primary care have had positive effect on overprescribing. 7 , 8 Other evidence suggests the implementation of opioid prescribing laws is not associated with decline in prescription opioids. 9 More importantly, there is credible proof the guideline left many chronic pain patients stranded with inadequate analgesic coverage.…”
Section: Introductionmentioning
confidence: 99%